Associations between RET tagSNPs and their haplotypes and susceptibility, clinical severity, and thyroid function in patients with differentiated thyroid cancer - He, Caiyun; Ma, Jiangjun; Jiang, Yongle; Su, Xuan; Zhang, Xiao; Chen, Weichao; Ye, Zulu; Deng, Tiancheng; Deng, Wenze; Yang, Ankui (PloS one, 2017)
It is unclear whether common genetic variants of the RET proto-oncogene contribute to disease susceptibility, clinical severity, and thyroid function in differentiated thyroid cancer (DTC). A total of 300 DTC patients and 252 healthy controls were enrolled in this study. Seven RET tagging single nucleotide polymorphisms were genotyped using the KASPar platform. Subgroup analysis showed that concomitant thyroid benign diseases were less likely to occur in DTC subjects with the rs1799939 AG or AG plus AA genotypes (odds ratio (OR) = 1.93 and 1.88, P = 0.009 and 0.011, respectively). A rare haplotype, CGGATAA, was associated statistically with a reduced risk of DTC (OR = 0.18, P = 0.001). Concerning the aggressive features of DTC, higher level of N stage was more likely to occur in subjects carrying the wild-type genotypes at rs1800860 site (for dominant model: OR = 0.48, P = 0.008). Another rare haplotype, CAAGCGT, conferred increased risk for the occurrence of distant metastasis (OR = 7.57, P = 0.009). Notably, higher thyroid stimulating hormone levels and lower parathyroid hormone levels were found in patients with rs2075912, rs2565200, and rs2742240 heterozygotes and rare homozygotes; similar results were observed between PTH levels and rs1800858. This study provided useful information on RET variants that should be subjected to further study.